Learning from Sustained Success: How Community-Driven Initiatives to Improve Urban Sanitation Can Meet the Challenges. (November 2016) - McGranahan, Gordon; Mitlin, Diana
Highlights: Collective action, coproduction, affordability and tenure enable sanitary progress. Two successful examples of sustained sanitation efforts are shown to achieve these. Other case studies illustrate obstacles to such success in other settings. Summary: Past research by one of the authors of this paper has identified four key institutional challenges that community-driven initiatives to improve sanitation in deprived urban settlements face: the collective action challenge of improving community sanitation; the coproduction challenge of working with formal service providers to dispose of the sanitary waste safely; the affordability challenge of reconciling the affordable with what is acceptable to both users and local authorities; and the tenure challenge of preventing housing insecurity from undermining residents' willingness to commit to sanitary improvement. In this article we examine how two well-documented, relatively successful and longstanding initiatives, the Orangi Pilot Project and an Alliance of Indian partners, met these challenges. They were met through social innovation, but also through the choice and development of sanitation technologies (simplified sewers for OPP and community toilet blocks for the Indian Alliance) that provided traction for the social innovations. We also explore more recent efforts by civil society partnerships in four African cities, demonstrating some of the difficulties they have faced in trying to overcome these challenges. No equivalent models have emerged, though there has been considerable progress against particular challenges in particular places. These findings confirm the importance of the challenges, and indicate that these are not just challenges for social organization, but also for technology design and choice. For example, the problem with household pit latrines is not that they cannot physically be improved to sufficiently, but that they are not well-suited to the social, economic and political challenges of sanitary improvement at scale. The findings also indicate that a low economic status and a tendency to treat sanitation as a private good not suitable for public support also makes the sanitation challenges difficult to overcome.